Young and Hungry? Employment Levels for Young People During Spring 2021 - John V. Winters (Institute of Labor Economics (IZA), 2021)
This article examines employment rates for persons in their teens and early 20s during April and May 2021 compared to April and May 2019. Employment rates for teens are significantly higher in Spring 2021 than in Spring 2019. However, individuals ages 20-24 experienced significantly lower employment rates in Spring 2021 than in Spring 2019. Differing employment patterns for these two age groups are unlikely to reflect childcare issues or lingering COVID-19 concerns. Restaurant employment rates suggest that weak labor demand is likely not the predominant factor. One plausible explanation is that teenagers are less influenced by generous unemployment insurance benefits.
Keywords: J2; 330; employment; labor supply; COVID-19; pandemic; young people; unemployment insurance